Foreign investment flows in a shifting geoeconomic landscape - Danish (South Centre, 2023)
The economic shocks from the pandemic and rising geoeconomic tensions have triggered an accelerated restructuring of foreign investment flows in global value chains. As the previous determinants of foreign investment are rapidly changing, many new risks and opportunities abound for developing countries looking to attract FDI into their economies. This paper therefore looks at some of the important issues affecting foreign investment flows to developing countries both now and in the future. It then lays out some policy imperatives which can help countries ensure that the inbound foreign investment is responsible, sustainable and contributes to achieving the national development priorities.
10419/283428
Keywords: Graue Literatur; Climate Change; COVID-19; Digital Transformation; Foreign Direct Investment (FDI); Global Investment Regime; Global Value Chains (GVCs); Human Rights Due Diligence (HRDD); International Investment Agreements (IIAs); International Investment Regime; Investment; Investor-State Dispute Settlement (ISDS) System; ISDS Reform; Pandemic; Sustainable Development